2013
DOI: 10.4172/2329-6895.1000140
|View full text |Cite
|
Sign up to set email alerts
|

CT Angiography and Presentation NIH stroke Scale in Predicting TIA in Patients Presenting with Acute Stroke Symptoms

Abstract: Patient candidacy for acute stroke intervention, is currently assessed using brain computed tomography angiography (CTA) evidence of significant stenosis/occlusion (SSO) with a high National Institutes of Health Stroke Scale (NIHSS) (>6). This study examined the association between CTA without significant stenosis/occlusion (NSSO) and lower NIHSS (≤ 6) with transient ischemic attack (TIA) and other good clinical outcomes at discharge. Patients presenting <8 hours from stroke symptom onset, had an NIHSS assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…With the development of new neuroimaging modalities, such as CTA, MRA, and DSA, increasing imaging records on TIA can be found, especially with the application of MRA, which can be used to improve the determination of patients with high risk of having recurrent stroke or TIA [ 4 ]. Application of neuroimaging modalities have revealed that stenosis or occlusion of a large proximal intracranial or extracranial symptomatic artery were significantly associated with recurrent stroke/TIA [ 4 8 ]. Most previous studies concentrated on the imaging results of brain tissues and vascular lesions, and the degree of artery stenosis and plaques, but few researchers have paid attention to the difference of vascular characteristics between TIA and infarction patients.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of new neuroimaging modalities, such as CTA, MRA, and DSA, increasing imaging records on TIA can be found, especially with the application of MRA, which can be used to improve the determination of patients with high risk of having recurrent stroke or TIA [ 4 ]. Application of neuroimaging modalities have revealed that stenosis or occlusion of a large proximal intracranial or extracranial symptomatic artery were significantly associated with recurrent stroke/TIA [ 4 8 ]. Most previous studies concentrated on the imaging results of brain tissues and vascular lesions, and the degree of artery stenosis and plaques, but few researchers have paid attention to the difference of vascular characteristics between TIA and infarction patients.…”
Section: Introductionmentioning
confidence: 99%